Numerical investigations on the heat transfer characteristics of tube in tube helical coil heat exchanger. (November 2019) - Sheeba, A; Mathew, P; Jose, Prakash M
Abstract: Heat transfer characteristics of a tube in tube helical heat exchanger in the laminar flow regime is analysed numerically. Numerical scheme is validated with the experimental results reported in literature. The effect of helix angle on the overall heat transfer coefficient is analysed. The overall heat transfer coefficient increases with Dean number and its rate of increase at higher Dean number is low. The rate of heat transfer is maximum at a helix angle of 27°. Simulation studies show that the secondary flows that originate in a coiled tube due to curvature and torsion produce an additional transport of the fluid over the cross section of the pipe. The overall heat transfer coefficient increases with increase in inner diameter.